2006
DOI: 10.1016/j.ygeno.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Canine RPGRIP1 mutation establishes cone–rod dystrophy in miniature longhaired dachshunds as a homologue of human Leber congenital amaurosis

Abstract: Cone-rod dystrophy 1 (cord1) is a recessive condition that occurs naturally in miniature longhaired dachshunds (MLHDs). We mapped the cord1 locus to a region of canine chromosome CFA15 that is syntenic with a region of human chromosome 14 (HSA14q11.2) containing the retinitis pigmentosa GTPase regulator-interacting protein 1 (RPGRIP1) gene. Mutations in RPGRIP1 have been shown to cause Leber congenital amaurosis, a group of retinal dystrophies that represent the most common genetic causes of congenital visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
111
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 46 publications
1
111
1
4
Order By: Relevance
“…The cord1 locus was mapped to a region of canine chromosome 15 containing the RPGRIP1 gene. Genome sequencing identified a 44-nucleotide insertion in exon 2 of RPGRIP1 that alters the reading frame and introduces a premature stop codon (Mellersh et al 2006). In the initial study that identified the RPGRIP1 mutation, affected and carrier dogs within an extended inbred pedigree were homozygous and heterozygous, respectively, for the mutation (Mellersh et al 2006).…”
Section: Animal Modelsmentioning
confidence: 99%
“…The cord1 locus was mapped to a region of canine chromosome 15 containing the RPGRIP1 gene. Genome sequencing identified a 44-nucleotide insertion in exon 2 of RPGRIP1 that alters the reading frame and introduces a premature stop codon (Mellersh et al 2006). In the initial study that identified the RPGRIP1 mutation, affected and carrier dogs within an extended inbred pedigree were homozygous and heterozygous, respectively, for the mutation (Mellersh et al 2006).…”
Section: Animal Modelsmentioning
confidence: 99%
“…At 52 wk, most affected animals still had recordable electroretinography (ERG) responses. In the MLHDs, the ERG responses were nonrecordable already at the age of 40 wk (Mellersh et al 2006).…”
Section: Discussionmentioning
confidence: 91%
“…Mutations in RPGRIP1, however, have been reported to be a cause of LCA (Dryja et al 2001;Gerber et al 2001), while mutations causing residual RPGRIP1 activity may lead to phenotypes such as RP or crd, which are less severe than LCA (Cremers et al 2002). Some RPGRIP1 gene mutations are also associated with recessive crd in human (Hameed et al 2003) and dog (Mellersh et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations